Long-term results of hip arthroplasty in ambulatory patients with cerebral palsy - Schröder, Kerstin; Hauck, Christian; Wiedenhöfer, Bernd; Braatz, Frank; Aldinger, Peter (International orthopaedics, 2010)
Osteoarthritis (OA) secondary to dislocation and dysplasia is a common problem in patients with cerebral palsy. The purpose of this study was to evaluate the results of total hip replacement (THR) in ambulatory patients with cerebral palsy.